Peran Kepemimpinan Kepala Sekolah Dalam Usaha Meningkatkan Kedisiplinan Guru Di Mts Terpadu Al-Huda Cililin - Bachtiar, Renata Aghnia; Purwanda, Eka (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the role of the principal in improving teacher discipline at MTs Terpadu Al-Huda Cililin, analyze the factors that influence it, and identify the obstacles faced. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, then analyzed qualitatively. The results showed that the principal plays an important role in shaping teachers' discipline culture through transformative leadership that encourages motivation and professional development. This role can be seen in exemplary leadership, effective communication, and providing motivation and inspiration. Improved teacher discipline has an impact on a more conducive learning atmosphere, increased student learning motivation and better academic achievement. It is concluded that the principal's leadership is a crucial factor in improving discipline and learning quality in the school.